Assessment of bacteriological profile and wound infection in open and laparoscopic gall bladder surgery - Raja, Faizan; Gani, Mubashir; Illahi, Mir Fazil; Rather, Ajaz Ahmad (International Journal of Research in Medical Sciences, 2024)
Background: Cholecystectomy is one of the most frequent types of abdominal surgery performed in the world. Generally, there is minimal risk of serious postoperative complications. One of the complications is Surgical Site Infection, which can be caused by bile leakage and intraoperative contamination. Methods: This prospective study was conducted in department of General Surgery, SKIMS medical college Srinagar, from June 2020 to July 2023 comprising of 100 patients. All patients undergoing the procedure were observed for wound infection. Results: A total of 100 patients were studied with female to male ratio of 2:3. The mean age was 50.24±12.25 with 54% elderly patients. The average hospital stay was 4.02±07. 88% subjects belonged to ASA II Category with Hypertension and hyperthyroidism as common comorbidity. 11 patients got wound infection including 9 from open cholecystectomy and 02 from laparoscopic cholecystectomy with most patients belonging to elderly age group. Wound culture was positive in 9 out of 11 subjects of open cholecystectomy. E. coli was seen to be a major causal bacterial agent. Bile culture was positive in 8 patients. Both genders were almost equally affected by wound infection. Meropenem, Ceftriaxone, Gentamicin and Amikacin showed the highest number of antibiotic sensitivities tested in case of wound cultures. Conclusions: The prevalence of positive wound culture in uncomplicated laparoscopic cholecystectomy is low as compared to open procedure. Elderly age, co-morbid patients, patients who had history of jaundice, recent history of cholecystitis were at higher risk of wound infections.